Interplay between the Mediterranean diet and C-reactive protein genetic polymorphisms towards inflammation in adolescents. Issue 6 (June 2020) - Arouca, Aline B.; Meirhaeghe, Aline; Dallongeville, Jean; Moreno, Luis A.; Lourenço, Gustavo Jacob; Marcos, Ascensión; Huybrechts, Inge; Manios, Yannis; Lambrinou, Christina-Paulina; Gottrand, Frederic; Kafatos, Anthony; Kersting, Mathilde; et al.
Summary: Aim: From a nutrigenetics perspective, we aim to investigate the moderating role of the Mediterranean diet and each of its subgroups in the association between C-reactive protein ( CRP ) gene polymorphisms and CRP blood concentration in adolescents. Methods: In 562 adolescents (13–17 y) of the European HELENA study, data was available on circulating CRP levels as inflammatory biomarker, three CRP gene SNPs (rs3093068, rs1204, rs1130864), food intake determined by a self-administered computerized 24 h-dietary recall for 2 days, and body composition. A 9-point Mediterranean diet score and each food subgroup were tested as moderator via SNP*diet interaction. Analyzes were adjusted for age, sex, puberty, adiposity and socioeconomic status. Results: The minor allele frequencies of rs3093068 and rs1130864 SNPs (GG and TT, respectively) were associated with higher CRP concentrations, while rs1205 (CT/TT) was associated with lower CRP concentrations. There were significant interactions between rs3093068 and Mediterranean diet (B = −0.1139, p  = 0.011), or the fish food subgroup (B = −0.0090, p  = 0.022), so that those with the highest genetic CRP risk underwent the highest CRP attenuation by a healthier diet. Although the effect of diet and SNP was substantial, the explained variance by interaction was only 1%. Conclusion: Greater adherence to the Mediterranean diet and particularly its fish component was associated with a lower CRP blood concentrations especially in those at highest genetic risk due to the rs3093068 SNP.